2019
DOI: 10.1111/ans.15085
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body mass index on utilization of selected hospital resources for four common surgical procedures

Abstract: Background Evidence about the impact of obesity on surgical resource consumption in the Australian setting is equivocal. Our objectives were to quantify the prevalence of obesity in four frequently performed surgical procedures and explore the association between body mass index (BMI) and hospital resource utilization including procedural duration, length of stay (LOS) and costs. Methods A retrospective cohort study of patients undergoing four surgical procedures at a tertiary referral centre in New South Wale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…More than half of American adults are overweight or obese, and this proportion is increasing [12,13]. Studies have shown that obesity is associated with an increased morbidity in cardiovascular disease, diabetes, and depression [14][15][16], increasing hospital length of stay and medical costs [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…More than half of American adults are overweight or obese, and this proportion is increasing [12,13]. Studies have shown that obesity is associated with an increased morbidity in cardiovascular disease, diabetes, and depression [14][15][16], increasing hospital length of stay and medical costs [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…20 Participants with an elevated BMI have largely been excluded from or underrepresented in prehabilitation studies. [21][22][23][24] However, they comprise a large proportion of elective case waiting lists, particularly orthopaedic and gynaecology lists 25 and therefore the total surgical inpatient population. Although we did not measure postoperative outcomes, one prehabilitation programme focusing on weight reduction showed meaningful decreases in rates of surgical and cardiovascular complications postoperatively.…”
Section: Medical Outcomesmentioning
confidence: 99%
“…Obesity is an increasingly common problem in many countries (Twells et al, 2014 ) with many potential health implications in the perioperative period (Nightingale et al, 2015 ). Rates of obesity in surgical patients have been reported to vary between 35 and 70% depending on the type of surgery and can be twice the background rate of the general population (Mullen et al, 2009 ; AIHW, 2019 ; STARSurg-Collaborative, 2016 ; Hamlin et al, 2013 ; Freckelton et al, 2019 ; Harms et al, 2007 ). Preoperative problems include optimisation of concurrent medical conditions such as obstructive sleep apnoea (Chung et al, 1999 ; Abdullah & Chung, 2014 ).…”
Section: Introductionmentioning
confidence: 99%